The influence of athletes’ gratitude on burnout: the sequential mediating roles of the coach–athlete relationship and hope - Liangshan Dong; Shisi Zou; Rong Fan; Bin Wang; Lv Ye (Frontiers in Psychology, 2024)
BackgroundAthlete burnout is a widespread psychological syndrome in competitive sports, negatively impacts athletes’ competitive state and hampers the healthy development of sports organizations. With the rise of positive psychology, exploring the mechanisms of athlete psychological fatigue through the lens of psychological capital has become a focal point of recent research. This study introduces gratitude, a key element of psychological capital in positive psychology, to examine its effect on athlete burnout and its mechanism of action, with a particular focus on the sequential mediating roles of the coach-athlete relationship (CAR) and hope.MethodA cross-sectional study design was utilized, involving 483 active Chinese athletes from national training teams and professional sports teams. The sample comprised both male (n=251) and female (n=232) athletes, with an average age of 19.24 ± 3.99 years. Participants were asked to complete self-administered questionnaires, including the Gratitude Questionnaire, CAR Questionnaire, Hope Questionnaire, and Athlete Burnout Questionnaire. Structural equation modeling in AMOS 24.0 and descriptive statistics and correlation analyses in SPSS 20.0 were employed for data analysis.ResultsThe study revealed significant associations between athlete gratitude, CAR, hope, and athlete burnout. Notably, gratitude was found to both directly and indirectly (via CAR and hope) influence burnout levels among athletes, suggesting a sequential mediation effect.ConclusionThe findings highlight the importance of positive psychological constructs in buffering against athlete burnout. Specifically, gratitude, alongside a supportive CAR and elevated levels of hope, may play crucial roles in mitigating burnout symptoms. These insights offer promising directions for the development of targeted intervention strategies aimed at fostering athlete well-being and performance, advocating for the integration of positive psychology principles in the management and prevention of athlete burnout.